An analysis of the use of DNS for malicious payload distribution - Dube, Ishmael (Rhodes University, Faculty of Science, Department of Computer Science, 2019)
The Domain Name System (DNS) protocol is a fundamental part of Internet activities that can be abused by cybercriminals to conduct malicious activities. Previous research has shown that cybercriminals use different methods, including the DNS protocol, to distribute malicious content, remain hidden and avoid detection from various technologies that are put in place to detect anomalies. This allows botnets and certain malware families to establish covert communication channels that can be used to send or receive data and also distribute malicious payloads using the DNS queries and responses. Cybercriminals use the DNS to breach highly protected networks, distribute malicious content, and exfiltrate sensitive information without being detected by security controls put in place by embedding certain strings in DNS packets. This research undertaking broadens this research field and fills in the existing research gap by extending the analysis of DNS being used as a payload distribution channel to detection of domains that are used to distribute different malicious payloads. This research undertaking analysed the use of the DNS in detecting domains and channels that are used for distributing malicious payloads. Passive DNS data which replicate DNS queries on name servers to detect anomalies in DNS queries was evaluated and analysed in order to detect malicious payloads. The research characterises the malicious payload distribution channels by analysing passive DNS traffic and modelling the DNS query and response patterns. The research found that it is possible to detect malicious payload distribution channels through the analysis of DNS TXT resource records.
Keywords: Internet domain names; Computer networks -- Security measures; Computer security; Computer network protocols; Data protection